Gereja dan Teknologi: Analisis Digital Ecclesiology Penatalayan di GKI SOKA - Delahoya, Samuel (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2025)
The church is a place of worship for Christians, both past and present. The development of science and technology, especially in worship and church administration, has certainly made everything more flexible and dynamic. The development of the congregation's faith is reviewed from science and technology studies which focus on developments in science and technology in the implementation of church stewardship as well as reflections and responses through interviews with the GKI Soka Salatiga congregation. This research aims to see the development of faith in the congregation through individual reflective statements about worship interspersed with technology from the perspectives of youth, parents, church council and the elderly. The method used is descriptive qualitative research with two approaches, both the latest literature and interviews so that the data obtained and analysis through the literature data can find meaning and answer one main question in this research, namely what about reflection. The faith of the congregation sees the development of science and technology in the church, especially at GKI SOKA.